Kur'an. Arapça. (İstanbul : San‘a)
216, 564 sayfa, 183 sayfa
Keywords: “A scholarly study of the copy (Mushaf) of the Holy Quran which is attributed to the time of Ali b. Abi Talib and located in Sana’a, Yemen. It comes out as a third publication in IRCICA’s series of editions of oldest copies of the Quran. The copy is located at the Grand Mosque of Sana’a. The study gives a concise history of the dissemination of the Holy Quran through its copies and of the developments relating to script, orthography, punctuation, locations, etc. of the copies. It examines, describes and analyses the characteristics of the Sana’a copy as to script, orthography, binding, etc.“ -- Yayıncı.